A critical evaluation of the role of ethylene and MADS transcription factors in the network controlling fleshy fruit ripening. Issue 4 (8th November 2018) - Li, Shan; Chen, Kunsong; Grierson, Don
Abstract : Contents Summary 1724 I. Introduction 1725 II. Ripening genes 1725 III. The importance of ethylene in controlling ripening 1727 IV. The importance of MADS‐RIN in controlling ripening 1729 V. Interactions between components of the ripening regulatory network 1734 VI. Conclusions 1736 Acknowledgements 1738 Author contributions 1738 References 1738 Summary: Understanding the regulation of fleshy fruit ripening is biologically important and provides insights and opportunities for controlling fruit quality, enhancing nutritional value for animals and humans, and improving storage and waste reduction. The ripening regulatory network involves master and downstream transcription factors (TFs) and hormones. Tomato is a model for ripening regulation, which requires ethylene and master TFs including NAC‐NOR and the MADS‐box protein MADS‐RIN. Recent functional characterization showed that the classical RIN‐MC gene fusion, previously believed to be a loss‐of‐function mutation, is an active TF with repressor activity. This, and other evidence, has highlighted the possibility that MADS‐RIN itself is not important for ripening initiation but is required for full ripening. In this review, we discuss the diversity of components in the control network, their targets, and how they interact to control initiation and progression of ripening. Both hormones and individual TFs affect the status and activity of other network participants, which changes overall network signaling and ripening outcomes. MADS‐RIN, NAC‐NOR and ethylene play critical roles but there are still unanswered questions about these and other TFs. Further attention should be paid to relationships between ethylene, MADS‐RIN and NACs in ripening control.